KONTRIBUSI PENERAPAN METODE PEMBELAJARAN DAN AKTIVITAS BELAJAR TERHADAP HASIL BELAJAR FIKIH SISWA MADRASAH TSANAWIYAH NEGERI TANAH JAWA KABUPATEN SIMALUNGUN - Budi Suemdi (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2019)
This study aims to find out and emphasize: (1) the positive and significantcontribution of the application of learning methods to Jurisprudencelearning outcomes, (2) the positive and significant contribution of learningactivities to Jurisprudence learning outcomes, and (3) the positive andsignificant contribution of the application of learning methods andactivities learn together about the results of Jurisprudence learning. Thisresearch is quantitative research with correlation research methods. Thepopulation in this study were all students of class VIII consisting of 6classes with a total of 172. Samples totaling 35% of students totaling 205 is71.75 were rounded up to 72 students taken randomly. The data collectioninstruments used were questionnaires and tests. The data analysis used iscorrelation and regression. The research findings show: (1) there arepositive and significant contributions between the application of learningmethods and learning outcomes with a correlation number 0.354 with theregression line equation Ŷ = 71.60 + 0.23X1, (2) there are positive andsignificant contributions between learning activities and outcomes studywith a correlation number of 0.473 with the regression line equation Ŷ =68.96 + 0.28X2. and (3) there are positive and significant contributionsbetween the application of learning methods and learning activities withlearning outcomes with a correlation number of 0.549 with the regressionline equation Ŷ = 138.80 + 0.18X1 + 0.25X2. Effective contribution of thevariable of the application of learning methods to learning outcomes is9.90%, while the effective contribution of the learning activity variable tolearning outcomes is 20.00%